Early dentofacial features of Class II malocclusion: A longitudinal study from the deciduous through the mixed dentition - Baccetti, Tiziano; Franchi, Lorenzo; McNamara, James A.; Tollaro, Isabella (American journal of orthodontics and dentofacial orthopedics, 1997)
A group of 25 untreated subjects with Class II malocclusion in the deciduous dentition (featuring the concomitant presence of distal step, Class II deciduous canine relationship, and excessive overjet) was compared with a control group of 22 untreated subjects with ideal occlusion (flush terminal plane, Class I deciduous canine relationship, minimal overbite, and overjet) at the same dentitional stage. The subjects were monitored during a 2 ½-year period in the transition from the deciduous to the mixed dentition, during which time no orthodontic treatment was provided. Occlusal analysis of the Class II group in the deciduous dentition revealed an average interarch transverse discrepancy due to a narrow maxillary arch relative to the mandible. All occlusal Class II features were maintained or became exaggerated during the transition to the mixed dentition. The skeletal pattern of Class II malocclusion in the deciduous dentition typically was characterized by significant mandibular skeletal retrusion and mandibular size deficiency. During the period examined, cephalometric changes consisted of significantly greater maxillary growth increments and smaller increments in mandibular dimensions in the Class II sample. Moreover, a greater downward and backward inclination of the condylar axis relative to the mandibular line, with consequent smaller decrements in the gonial angle, were found in the Class II group, an indication of posterior morphogenetic rotation of the mandible in patients with Class II malocclusion occurring during the period examined. The results of this study indicate that the clinical signs of Class II malocclusion are evident in the deciduous dentition and persist into the mixed dentition. Whereas treatment to correct the Class II problem can be initiated in all three planes of space (e.g., RME, extraoral traction, functional jaw orthopedics), other factors such as patient cooperation and management must also be taken into consideration before early treatment is started. (Am J Orthod Dentofac Orthop 1997;111:502-9.)